2020
DOI: 10.1016/j.jjcc.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

University hospitals, general hospitals, private clinics: Place-based differences in patient characteristics and outcomes of AF—A SAKURA AF Registry Substudy

Abstract: A B S T R A C TBackground: Relations between characteristics and outcomes of patients in Japan with atrial fibrillation (AF) and the type of medical facility providing their outpatient care are unclear. Methods and results: We compared patient characteristics and outcomes between 2 university hospitals (n = 1178), 20 general hospitals (n = 1308), and 41 private clinics (n = 751) (follow-up: 39.3 months) in the prospective SAKURA AF Registry. Private clinic patients were significantly older than university hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The standardized definitions may be warranted to define CSIDs. Although diagnostic workups were done in the two study participating facilities as a university hospital and affiliated center [ 50 ], the diagnosis of CSIDs was based on medical records. Data are lacking on medical therapy before and after the hospitalization for acute MI, including immunomodulators and disease modifying anti-rheumatic drugs for CSIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized definitions may be warranted to define CSIDs. Although diagnostic workups were done in the two study participating facilities as a university hospital and affiliated center [ 50 ], the diagnosis of CSIDs was based on medical records. Data are lacking on medical therapy before and after the hospitalization for acute MI, including immunomodulators and disease modifying anti-rheumatic drugs for CSIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were enrolled in the SAKURA AF Registry between September 1, 2013 and December 31, 2015 and have been followed up for at least 2 years since their enrollment (final follow-up ended in December 31, 2017). The study design, data collection, and baseline characteristics have been reported previously [11,14,15,17]. Patient eligibility for enrollment in the registry included the following: a diagnosis of nonvalvular AF based on a 12-lead electrocardiography (ECG) recording, 24-h Holter ECG recording, or event-activated ECG recording; an age !20 years; and treatment (either just initiated or already in place) with any anticoagulant drug for stroke prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome those limitations of VKAs, direct oral anticoagulants (DOACs) have been developed, and randomized control trials [7][8][9][10] and several Japanese registries [11][12][13] have shown the benefit of these DOACs in reducing the risk of bleeding complications and/or stroke events in AF patients. DOACs are advantageous over VKAs/warfarin in terms of the clinical benefits and convenience [7][8][9][10][11][12][13][14][15][16][17] and thus, we found that Japanese patients given a DOAC were satisfied with their treatment for the burden assessed by a satisfaction questionnaire [anticoagulation-specific Anti-Clot Treatment Scale (ACTS)] [14]. Nonetheless, unexpectedly, the benefit satisfaction assessed by the ACTS appeared to be modestly lower than that in those given warfarin [14].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation